THE IMPORTANCE OF ORGANIZING CREATIVE GAMES WITH PRESCHOOL CHILDREN IN DEVELOPMENT CENTERS - Salimova Dilmira Farkhodovna (Modern American Journals, 2025)
This article discusses the preparation of the necessary equipment in advance and the interactive methods used in the games to arouse children's interest in education and to make the games interesting through creative games organized by educators in developmental environments in preschool educational organizations.
Keywords: Preschool education, game, creative, plot-role-playing game, educator-pedagogue, preschool age, education, team game, motivation.